The effect of Mn2Sb2 and Mn2Sb secondary phases on magnetism in (GaMn)Sb thin films (2020)
In this work, a detailed study of structural, electrical and magnetic characterization of (GaMn)Sb diluted magnetic semiconductors (DMS) is presented. (GaMn)Sb thin films were grown by DC magnetron co-sputtering method as an innovative procedure to fabricate III-V DMS. The presence of unusual Mn2Sb2 and Mn2Sb secondary phases, induced by substrate temperature and deposition time, were revealed through XRD measurements. Magnetization measurements allow determining crossover between a paramagnetic-like to a ferromagnetic-like behavior controlled by secondary phases. It was found that both, the magnetic remanence and magnetic coercivity, increases with substrate temperature. Interestingly, the magnetic response is paramagnetic at lower deposition times and substrate temperatures, and XRD measurements suggest the absence of Mn2Sb and Mn2Sb2 in secondary phases. For longer deposition times or higher substrate temperature, XRD shows the presence of Mn2Sb2 and Mn2Sb phases and ferromagnetic-like behavior. The DC resistivity of our samples was characterized and the carrier density was determined by Hall measurements and, in contrast with the reported in other studies, found them to be a p-type semiconductor with carrier densities as big as one order of magnitude larger than reported values. From the ferromagnetic-like samples, evidence of an anomalous Hall-effect in the sample was found, with higher magnetic saturation and a anomalous Hall conductivity of 2380 S/cm. All the results point to a contribution of the secondary phases to the overall magnetic response of the samples used, and suggest the importance of studying the formation of secondary phases in the growth of DMS, especially, for the case of (GaMn)Sb where Mn ion can have multiple oxidation states. Copyright: © 2020 Calderón et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.